The heritage culture restoration to engage in bio-cultural diversification/ Zulaika Mohamad ... [et al.] - Mohamad, Zulaika; Abdul Latif, Faridatul Akma; Mat Isa, Masbiha; Mohamed Ali, Salina (Universiti Teknologi MARA, Perak, 2024)
The ecology and cultural legacy of a community define its potential for development. Combining philosophy and thinking fosters the preservation of historical sites, environmental protection, and the capacity to display the diversity of bio-cultures.. This case study is directed towards the issues of the state government, the fishermen's market organization, and fishing villages. It is also possible to identify this through reasonable issues that fall under the environmental, social, and physical challenges groups. This article discussed the economic circumstances in Kuala Kedah and offered cultural insights. The cultural heritage and ecology retreat, which fosters a feeling of place and promotes the sustainability of a heritage culture town, brought attention to the significance of this article. The main goals of this study are to look into the uniqueness and distinctiveness of the relationship between local identity, legacy, and the economic revival of Seberang Kota through inventory and analysis.The findings and information from the inventory and analysis are combined to identify possible areas for environmental preservation and cultural enhancement. The final half of the article included some design guidance that is essential for anticipating the rules for organising and carrying out this research. To support sustainable living opportunities for the local population and the preservation of the surrounding environment for tourists, which will entice them to participate in environmental and cultural activities, this article offers a plan for preserving and enhancing Seberang Kota's distinctive character and identity as a cultural heritage village.